2018
DOI: 10.1007/s00223-018-0401-9
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Rheumatic Diseases: Anti-rheumatic Drugs and the Skeleton

Abstract: Osteoporosis in rheumatic diseases is a very well-known complication. Systemic inflammation results in both generalized and localized bone loss and erosions. Recently, increased knowledge of inflammatory process in rheumatic diseases has resulted in the development of potent inhibitors of the cytokines, the biologic DMARDs. These treatments reduce systemic inflammation and have some effect on the generalized and localized bone loss. Progression of bone erosion was slowed by TNF, IL-6 and IL-1 inhibitors, a JAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 91 publications
1
23
0
Order By: Relevance
“…Interestingly, the use of denosumab seems neither related to a higher risk for inflammatory activity (relapse of IBD), nor for an increased risk for infectious diseases [79]. This has been subject of study in rheumatoid arthritis but not in IBD [80], and effects on bone formation more than on bone resorption have been proposed when observing elevated concentrations of bone-specific alkaline phosphatase [81]. In addition, denosumab use seems to be associated with a rebound effect following discontinuation of therapy which may be considered to be a major flaw when using this drug in the relative young IBD population [82].…”
Section: Denosumab and Other New Bone Health-improving Agentsmentioning
confidence: 99%
“…Interestingly, the use of denosumab seems neither related to a higher risk for inflammatory activity (relapse of IBD), nor for an increased risk for infectious diseases [79]. This has been subject of study in rheumatoid arthritis but not in IBD [80], and effects on bone formation more than on bone resorption have been proposed when observing elevated concentrations of bone-specific alkaline phosphatase [81]. In addition, denosumab use seems to be associated with a rebound effect following discontinuation of therapy which may be considered to be a major flaw when using this drug in the relative young IBD population [82].…”
Section: Denosumab and Other New Bone Health-improving Agentsmentioning
confidence: 99%
“…The RANK-RANKL system has been extensively studied in the context of osteoporosis related to chronic inflammatory disease. In fact, rheumatic diseases such as rheumatoid arthritis (RA) and ankylosing spondylitis are frequently associated with bone loss, both localized and systemic, and are characterized by an increased risk of osteoporotic fractures in all age groups [33] (Fig. 1).…”
Section: Osteoimmunologymentioning
confidence: 99%
“…Studies evaluating the skeletal effects of rituximab in rheumatological patients reported conflicting results. One study on rituximab treatment in patients with rheumatoid arthritis (RA), described an increase in lumbar spine BMD (bone mineral density) irrespective of clinical response, whereas in the femur, rituximab merely prevented bone loss, and only in responders (6). Another study suggested that treatment with rituximab reduced osteoclast activity as assessed by serum markers of bone resorption (7), and a recent study, also in RA patients (8), demonstrated a significant reduction in the femoral BMD with no effect in the spine.…”
Section: Introductionmentioning
confidence: 99%